PENGARUH PENERAPAN SISTEM MANAJEMEN MUTU INTERNATIONAL ORGANIZATION FOR STANDARDIZATION (ISO 9001:2008) TERHADAP KINERJA PEGAWAI PADA PT ASIA SAKTI WAHID FOODS MANUFACTURE MEDAN - Asti Dianputri (Jurnal Niaga & Bisnis (e-journal), 2014)
This research aims to analyze the effect of the application of Quality Management System ISO 9001: 2008 with the performance of employees at PT Asia Sakti Wahid Foods Manufacture. The results of this research are expected to provide benefit as references and material input for PT Asia Sakti Wahid Foods Manufacture. This research is a form of associative research, using a quantitative approach. Population in this research is employees at the office of PT Asia Sakti Wahid Foods Manufacture which consisted of 230 people. By using the sample Slovin Formula, these studies amounted to 70 people. Data collection techniques using question form/questionnaire and documentation. Validity test done by comparing the value of probability and reliability test done by looking at the value of Cronbach Alpha. A classic assumption test used is the test of normality and heterokedastisitas test. Then proceed with the analysis of data correlation Pearson Product Moment, simple linear regression, and hypotheses test. Based on the research results obtained that the correlation between the performance of the Quality Management System is 0,426, meaning a direct relationship. Regression equation of the Model is Y = 32,363 + 0, 417X. From the regression equation, obtained constant` 32,363 and constant coefficient of regression Quality Management System variable is 0,417. Based on the results of test T concluded that the Quality Management System have an effect on the performance of employees at PT Asia Sakti Wahid Foods Manufacture. The R-Square value is 0,182. It means that 18,2 % variation performance determined by the role of the Quality Management System, while 81,8% the rest is influenced by variations of other variables that are not included in this research. Key words: Quality Management System (ISO 9001: 2008), the performance of employees.